Queen–worker conflict can drive the evolution of social polymorphism and split sex ratios in facultatively eusocial life cycles. (26th September 2019) - Quiñones, Andrés E.; Henriques, Gil J. B.; Pen, Ido
Abstract: Hamilton's idea that haplodiploidy favors the evolution of altruism—the haplodiploidy hypothesis—relies on the relatedness asymmetry between the sexes caused by the sex‐specific ploidies. Theoretical work on the consequences of relatedness asymmetries has significantly improved our understanding of sex allocation and intracolony conflicts, but the importance of haplodiploidy for the evolution of altruism came to be seen as minor. However, recently it was shown that haplodiploidy can strongly favor the evolution of eusociality, provided additional "preadaptations" are also present, such as the production of multiple broods per season and maternal ability to bias offspring sex ratios. These results were obtained assuming no influence of workers on the sex ratio, even though worker control of the sex ratio is known to occur. Here, we model the evolution of sex‐specific fratricide as a mechanism of worker control over the sex ratio. We show that fratricide can facilitate the initial evolution of helping. However, fratricide can also hamper the evolution of unconditional help. Instead, social polymorphism evolves a mixture of helping and dispersing offspring. Finally, we show that the co‐evolution of sex‐allocation strategies of workers (fratricide) and queens leads to a split production of the sexes, with some colonies specializing in males and others in females. Thus, the model predicts that fratricide spawns a diversity of co‐existing life cycles that strongly vary in degree of sociality and sex ratios.